Factors Affecting Biofilms Formation in Drinking Water Distribution Systems - Manuchar , Jihad Abdulla (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This article discusses the importance of microbiological safety in drinking water and the challenges drinking water treatment plants face in delivering a safe product. Biofilms, thin layers of microorganisms that adhere to surfaces and produce a slimy matrix of extracellular polymeric substances, can potentially cause health risks in drinking water if they contain harmful microorganisms. The article highlights the need for proper maintenance of the drinking water distribution system and regular testing for the presence of harmful microorganisms and other contaminants to minimize the risk of illness from biofilms. The study focuses on insufficient research on biofilms in drinking water distribution systems in Sulaimani City. It provides new and relevant information on the public health problems associated with their presence and describes current and emergent strategies for their control. The microbiological and Physio Chemical experiments were conducted on water samples from various water drinking sources in Sulaimani City to evaluate contamination of portable drinking water. Then, Most Probable Number (MPN) and Membrane Filtration methods were applied to collected water samples for the determination and presence of coliform bacteria in water. Moreover, Swab biofilm was employed within a different agar and distributed by an L shape. After that, 13 different physio-chemical tests were conducted on the previous experiments. Enterobacteriaceae had a moderately negative correlation (-0.764) with temperature and was statistically significant (Sig. = 0.000). Moreover, it was moderately positively correlated (0.416) with Chemical Oxygen Demand (COD) and statistically significant (Sig. = 0.038).